IMPLEMENTATION ANALYSIS OF SEKOLAH SIAGA KEPENDUDUKAN (SSK) IN EAST JAVA 2019 - Aliqul Abdiyah; Fonny Indri Hartanti; Yuly Sulistyorini (Universitas Airlangga, 2020)
One of the ways to synergize various parties in anticipating and overcoming problems as a result of population dynamics is to increase the role of teachers through the establishment of Sekolah Siaga Kependudukan (SSK). This study aims to analyze the implementation of the SSK in East Java in 2019. The analysis was using descriptive analysis method. Secondary data on the number of schools that have SSK program is obtained through the area of population control by National Board Population and Family Planning Representative in East Java. Primary data related to problems and solutions in schools associated with the implementation of the SSK program were obtained by in-depth interviews conducted with heads of sub-fields and staff working in the area of Population Control. In 2017, National Board of Population and Family Planning Representative of East Java initiated the formation of SSK in 3 districts and cities. From 2017 to August 2019, the number of schools in East Java that have participated in the SSK program were 58 Senior High Schools and 24 Junior High Schools. Only 20.8% of schools that have met the SSK's criteria of success, namely (1) have a decree on the formation (2) have a nameplate, (3) the establishment of a population corner, (4) the integration of population material on subjects in the form of Lesson Plan (LP), and (5) community-related activities. Implementing SSK program in East Java still needs to be improved, especially in forming population corner. Students follow the integration of SSK materials into school subjects and the presence of population-themed activities through advocacy and coordination with stakeholders in districts and cities. The SSK program also requires increased socialization of activities at schools.